Epidemiology of SARS-CoV-2 Infection Evaluated by Immunochromatographic Rapid Testing for the Determination of IgM and IgG Against SARS-CoV-2 in a Cohort of Mask Wearing Workers in the Metal-Mechanical Sector in an Area With a High Incidence of COVID-19 - Esposito, Susanna; Neglia, Cosimo; Affanni, Paola; Colucci, Maria Eugenia; Argentiero, Alberto; Veronesi, Licia; Messina, Giulia; Deolmi, Michela; Principi, Nicola, the Crown Study Group (Frontiers in Public Health, 2021)
Background: Although the diagnosis of new coronavirus 2019 (COVID-19) is made through the identification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in respiratory secretions by means of molecular methods, a more accurate estimation of SARS-CoV-2 circulation can be obtained by seroprevalence studies. The main aim of this study was to evaluate the true epidemiology of SARS-CoV-2 infection among workers in the metal-mechanical sector who never stopped working during the pandemic period in an area with a high incidence of COVID-19 and to define whether and how they could continue the work without appreciable risks during a second wave. Methods: A total of 815 metal-mechanical workers who had never stopped working even during the pandemic period in three different factories in the Emilia-Romagna Region, Italy, and who had always used face masks during working hours, underwent a capillary blood rapid test for the determination of IgM and IgG against SARS-CoV-2 (COVID-19 IgG/IgM Rapid test, PrimaLab, Modena, Italy). In the event of a positive test, a nasopharyngeal was performed and tested for the presence of SARS-CoV-2. Results: The detection of serum IgG/IgM against SARS-CoV-2 was significantly more common among workers employed in Parma (21/345, 6.1%) than among those employed in Calerno (7/242, 2.9%) or in Spilamberto (3/228, 1.3%) (p< 0.001). The analysis of the role of the different variables as predictors of seropositivity for IgG/IgM against SARS-CoV-2 revealed that the presence of specific antibodies was strictly associated with a previous history of COVID-19-like symptoms (odds ratio [OR] 3.95, 95% confidence interval [CI] 1.9-8.2) and household members with COVID-19-like symptoms (OR 2.20, 95% CI 1.04-4.82). Conclusion: This study shows that seropositivity to SARS-CoV-2 is low even among employees who did not interrupt their work during the lockdown phase in a region with a high incidence of COVID-19. The use of face masks appears effective in the avoidance of the transmission of SARS-CoV-2 in factories even in the presence of asymptomatic or mildly symptomatic workers, suggesting that work activities can continue if adequate infection control measures are used during a second wave.